Disrupting my whiteness towards inhabiting a race equity coaching perspective: A self-inquiry into race, whiteness, and its impact on my coaching practice - Fenella Trevillion (International Journal of Evidence Based Coaching and Mentoring)
In May 2020, global attention was on George Floyd’s murder. As a white person coaching people of colour, my response to this systemic racism was to draw attention to racism and coaching and bring my practice and values around race equity into greater alignment. Through internal reflection and action and, disrupting my whiteness, my worldview changed. By using the methodology of autoethnography and themed categorisation of my pivot points of change, it emerged that transformation came through critical reflection and recursive movement. This research tracks that development and illustrates my new perspective on race equity in coaching and supervision.